Actuarial senescence can increase the risk of extinction of mammal populations. Issue 1 (1st January 2015) - Robert, Alexandre; Chantepie, Stéphane; Pavard, Samuel; Sarrazin, François; Teplitsky, Céline
Abstract : Despite recent acknowledgement that senescence can have negative impact on survival and fertility in natural environments across a wide range of animal species, we still do not know if it can reduce the viability of wild endangered populations. Focusing on actuarial senescence (i.e., the decline of survival probabilities at old ages), we use species‐specific demographic information to project the extinction risk of wild populations of 58 species of mammals, accounting (or not) for senescence. Our projections reveal potential negative effects of aging on population viability, with an average decrease of 27% of the time to extinction and a potential deterioration of the population‐level projected conservation status in 10% of the species. Senescence is associated with particularly strong increases of the extinction risk in species with low mortality rates and long intervals between litters, independently of their place in the phylogeny, indicating that the pace of life history can be used to forecast the detrimental effects of aging on the viability of species. The aim of the various existing systems of classification of threatened species is to set conservation priorities based on assessments of extinction risk. Our results indicate that the quantitative effects of senescence on extinction are highly heterogeneous, which can affect the ranking of species and populations when setting conservation priorities. In mammals, based on life history traits of a few species, generic patterns of senescence can be incorporated into projection population models to minimize these biases in viability assessments.